Clinical Experience of Proteasome Inhibitor Bortezomib Regarding Efficacy and Safety in Severe Systemic Lupus Erythematosus: A Nationwide Study - Walhelm, Tomas; Gunnarsson, Iva; Heijke, Rebecca; Leonard, Dag; Trysberg, Estelle; Eriksson, Per; Sjöwall, Christopher (Frontiers in Immunology, 2021)
As treatment options in advanced systematic lupus erythematosus (SLE) are limited, there is an urgent need for new and effective therapeutic alternatives for selected cases with severe disease. Bortezomib (BTZ) is a specific, reversible, inhibitor of the 20S subunit of the proteasome. Herein, we report clinical experience regarding efficacy and safety from all patients receiving BTZ as therapy for SLE in Sweden during the years 2014−2020. 8 females and 4 males were included with a mean disease duration at BTZ initiation of 8.8 years (range 0.8−20 years). Renal involvement was the main target for BTZ. Reduction of global disease activity was recorded by decreasing SLEDAI-2K scores over time and remained significantly reduced at the 6-month (p=0.007) and the 12-month (p=0.008) follow-up visits. From BTZ initiation, complement protein 3 (C3) levels increased significantly after the 2nd treatment cycle (p=0.05), the 6-month (p=0.03) and the 12-month (p=0.04) follow-up visits. The urine albumin/creatinine ratio declined over time and reached significance at the 6-month (p=0.008) and the 12-month follow-up visits (p=0.004). Seroconversion of anti-dsDNA (27%), anti-C1q (50%) and anti-Sm (67%) was observed. 6 of 12 patients experienced at least one side-effect during follow-up, whereof the most common adverse events were infections. Safety parameters (C-reactive protein, blood cell counts) mainly remained stable over time. To conclude, we report favorable therapeutic effects of BTZ used in combination with corticosteroids in a majority of patients with severe SLE manifestations irresponsive to conventional immunosuppressive agents. Reduction of proteinuria was observed over time as well as seroconversion of some autoantibody specificities. In most patients, tolerance was acceptable but mild adverse events was not uncommon. Special attention should be paid to infections and hypogammaglobinemia.